Developing Software for Motivating Individuals with Intellectual Disabilities to do Outdoor Physical Activity - Torrado, Juan C.; Wold, Ida; Jaccheri, Letizia; Pelagatti, Susanna; Chessa, Stefano; Gomez, Javier; Hartvigsen, Gunnar; Michalsen, Henriette (Proceedings of the ACM/IEEE 42nd International Conference on Software Engineering: Software Engineering in Society, 2020)
People with intellectual disabilities (IDs) often have a sedentary lifestyle that can lead to long-term issues like cardiovascular diseases, diabetes, obesity and depression. Few games and apps promoting physical activity for people with IDs exist, and they do not have a focus on the motivational aspect. This paper aims to find how to develop software that can motivate people with IDs to do physical activity outdoors. For this purpose, we have followed a design and creation research strategy using several qualitative methods such as semi-structured interviews with health care workers, special education experts and software engineers; a focus group with occupational therapists, physical therapists and software engineers; and a preliminary pilot user test with 3 users and 2 caregivers aiming to a test of the software on the field and at the refinement of its specifications. Having social interaction during the physical activity turned out to be a major motivational aspect of the system, whereas rewards systems did not attract much of the users' attention. Regarding the adapted navigational assistance, easy-to-read text, visual communication and street-level pictures were the key features to achieve successful and understandable guidance outdoors for people with intellectual disabilities.